2019
DOI: 10.1021/acsomega.9b00198
|View full text |Cite
|
Sign up to set email alerts
|

Arylbenzofurans from the Root Bark of Morus alba as Triple Inhibitors of Cholinesterase, β-Site Amyloid Precursor Protein Cleaving Enzyme 1, and Glycogen Synthase Kinase-3β: Relevance to Alzheimer’s Disease

Abstract: Cholinesterase, β-site amyloid precursor protein cleaving enzyme 1 (BACE1), and glycogen synthase kinase-3β (GSK-3β) are the three main enzymes responsible for the early onset of Alzheimer’s disease (AD). The main aim of the present study was to delineate and accentuate the triple-inhibitory potential of arylbenzofurans from Morus alba against these enzymes. Overall, the enzyme inhibition assays demonstrated the prominence of mulberrofuran D2 as an inhibitor of AChE, BChE, BACE1, and GSK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 61 publications
(97 reference statements)
2
12
0
1
Order By: Relevance
“…These two compounds have been used as references in many studies on AChE and BACE-1 inhibition. The results showed that the biological activities of the positive controls in this study are comparative to previously published values [ 34 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 54%
“…These two compounds have been used as references in many studies on AChE and BACE-1 inhibition. The results showed that the biological activities of the positive controls in this study are comparative to previously published values [ 34 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 54%
“…These two compounds have been used as references in many studies on AChE and BACE-1 inhibition. The results show that the biological activities of the positive controls in this study are comparative to the previously published values [ 56 , 57 , 58 ]. On the other hand, the experimental assays also specified that AC12 had a higher activity than galantamine on AChE and all the synthesized chalcones exhibited the higher inhibiting effects than quercetin on BACE-1.…”
Section: Resultssupporting
confidence: 53%
“…Bromophenols 1 – 3 were accessed for their ability to inhibit self-induced Aβ 25–35 aggregations via the thioflavin T (ThT) fluorescence method, 53 with slight modifications. 54 In brief, Aβ 25–35 , lyophilized from 1mg/mL hexafluoro-2-propanol (HFIP) solution, was dissolved in 65% acetonitrile to obtain 0.4 mM stock solution. Then the stock solution of Aβ 25–35 was diluted by 2-fold in 69 mM phosphate buffer (pH 7.0).…”
Section: Methodsmentioning
confidence: 99%